The factors behind succesfull immigrant athletes - Erkkilä, Aku (2019)
Immigration today is a current topic. Since the Arab-Spring, a new influx of refugees has been flowing towards Europe. This wave of immigration has caused comprehensive debate on, whether and how these immigrants are accepted on the receiving end of the future host countries. As a social phenomenon immigration has been a source of strong political debate and rhetoric. The reasons why this research was conducted, was two dimensional; firstly, being able to acknowledge the opportunity immigration might present for additional success in sports for the host country, and secondly, this study to demonstrates sports participations effectiveness as a whole considering the integration process of immigrants. The aim of this research was to explore the reasons behind the apparent success of multicultural athletes. What is the background of their motivation to do well in sports? What kind of barriers are these athletes facing, how these barriers effect on the athletes? The method used for this study was a qualitative one, applying narrative research tools. The main source of data was gathered from 5 different immigrant based athletes autobiographies. These narratives were combined with interviews collected from various different sources, such as, documentaries, theme-based radio-shows - journals and existing literature relevant to the topic. The main results of the research were linked with the integration process and issues connected with the lack of various social capitals among immigrant athletes. During the process of integration, immigrant athletes experienced and had to cross various social barriers and obstacles. The integration process and facing the barriers occurred, differentiated the immigrant athletes in distinct ways in comparison to their host-country athletic peers. The main hypothesizes of this research, as factors behind successful immigrant athletes were generally connected with this differentiation and social heterogenation. In addition to differences in succeeding in elite-sports, the results of the research highlighted the positive role of sports participation as a whole, as an important tool in the integration process overall, as well as, in determining the immigrant's identity in a new social environment. The research was able to demonstrate some distinguish, combining features which could benefit the immigrant/multicultural based athlete. However, because the topic as itself is so diverse and complex, it is difficult to determine complete and general answers whether immigrants in a larger scale actually have an extra incentive to do well in sports. Having said this, according to the data gathered within this research, it can be concluded that the bicultural background of the selected athletes, influenced their athletic progress during different stages of their athletic life course. Mainly because of the narrative nature of the research methods, this study accomplishes to describe the topic with a deeper, inside knowledge. However, for further study a mixture of quantitative and qualitative research is recommended.